A comprehensive investigation of finding the best location for hot steam injection into the wet steam turbine blade cascade. (1st January 2020) - Aliabadi, Mohammad Ali Faghih; Lakzian, Esmail; Khazaei, Iman; Jahangiri, Ali
Abstract: In the power plant industry, a major part of energy losses in the thermodynamic cycle is related to the steam turbines, which are not made to work with wet steam flow, and the presence of the liquid phase causes efficiency reduction and mechanical damages such as erosion, which leads to high expenses due to the high cost of steam turbines. The present study used the hot steam injection (HSI) to decrease condensation loss and erosion rate. Location for HSI effects on the pressure distribution, Mach number, and liquid mass fraction of flow at the suction and pressure surfaces. For this purpose, several locations on suction and pressure sides were considered to select an appropriate location for injection. In this study, EEHIC (entropy generated, erosion rate, HSI ratio, inlet mass flow rate to the blade and condensation loss) method is used to select the most suitable HSI location. Results indicated that injecting on the suction side is more effective on mentioned parameters than the pressure side. HSI on the suction side (the lowest temperature in the center line of blade) decreased the condensation loss and erosion rate ratio by 81% and 99%, respectively, compared to the case of no injection. Highlights: Location for hot steam injecting (HSI) in turbine blade is studied. Five parameters are used to select the most suitable HSI location. . HSI from the suction side has a greater impact than that of the pressure side. HSI reduced the condensation loss and erosion rate ratio by 81% and 99%.